Changes in 6-minute walk test distance and heart rate walking speed index following a cardiovascular prevention and rehabilitation programme. (2nd April 2019) - Grove, Tim; Jones, Jennifer; Connolly, Susan
Abstract : Background/Aim: To employ a more robust evaluation using the heart rate walking speed index to determine if the improvement in the 6-minute walk test distance is related to a true physiological adaptation following a cardiovascular prevention and rehabilitation programme. Methods: In total, 39 patients at high risk of cardiovascular disease or with established vascular disease were evaluated. Patients attended supervised circuit training sessions for up to 12 weeks and they were encouraged to take part in a home exercise programme 2–3 times per week. Findings: Following a cardiovascular prevention and rehabilitation programme, there was a 40-metre + interquartile range 0–70 metres improvement in the 6-minute walk test distance (95% confidence interval (CI) 18.8–50 P =<0.001) with a subsequent reduction in the heart rate walking speed index (−2.7 + interquartile range −0.59 to 0 95% CI −0.4–0.8 P <0.001). There was a non-significant change in peak heart rate (–0.4 beats per minute 95% CI −1.8–2.6 P =0.69) and rating of perceived exertion (95% CI 0–1 P =0.4) between baseline and end-of-programme assessments. Conclusions: Heart rate walking speed index provides transparency on the physiological adaptations following a cardiovascular prevention and rehabilitation programme. Patients increased their 6-minute walk test distance by 40 metres and decreased their heart rate walking speed index by 2.7, which translates into a saving of three heart beats for every 100 metres walked or 45 heart beats for every mile walked.